Biomarcadores cardioinflamatórios em repouso e o efeito do exercício físico aeróbio agudo na resposta glicêmica e do lactato sanguíneo em adultos diabéticos do tipo 1 - Anaruma, Chadi Pellegrini [UNESP] (2014)
Type 1 Diabetes Mellitus (T1DM) is a disease characterized by hyperglycemia and associated with microvascular and macrovascular complications. Glycemic control is the primary goal in the treatment of T1DM. There is evidence that lactate, an important substrate in the metabolism of glucose also undergoes changes. In order to obtain information and to increase scientific knowledge, the present study aimed to evaluate the effect of acute aerobic exercise of moderate intensity in glycaemia and blood lactate in adults type 1 diabetics. We selected adult males, aged 18 to 35 who were divided into two groups, a control group without diabetes (CON , n=10) and another group of individuals with type 1 diabetes (T1DM, n=9). At the beginning of the protocol were evaluated anthropometric parameters (weight, height, body mass index), cardiovascular (blood pressure and resting heart rate) and biochemical (blood glucose (BG), HbA1C, serum creatinine (SC), malondialdehyde (MDA), superoxide dismutase (SOD) and nitrite/nitrate (NOx-)). In order to verify the aerobic capacity, a one mile walk test was performed on a treadmill and as an indirect measurement of VO2peak. After the initial analysis, a single session of aerobic exercise on a treadmill with intensity of 40-60% of HRreserve for a period of 30 minutes was performed. The glycemic response and the production of blood lactate were determined during the course of the exercise and after a period of 30 minutes, collected at T=0', 10', 20', 30', 40', 50' and 60'. After the intervention, the results were analyzed using the statistical software GraphPad Prism 5. Results are expressed as mean±SEM, value of p<0.05 was adopted. We found no significant differences in anthropometric and cardiovascular parameters, demonstrating a homogeneous group. All other biochemical parameters were altered in the T1DM group (BG: CON 88±2.7 vs. DM1 179±32.1 mg/dL; HbA1c: 4.8±0.1 vs. 8.4±0.5 %; SC: 1.1±0.04 vs. 0.9±0.05...